2005
DOI: 10.1155/2005/358658
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination-Like Syndrome In Crohn’s Disease After Infliximab Therapy

Abstract: An 18-year-old female patient with Crohn's disease involving the ileum and colon developed ankylosing spondylitis. After treatment of her spondylitis with multiple infliximab infusions, new onset of neurological symptoms developed, accompanied by detection of an abnormal white matter signal change on magnetic resonance imaging examination. Although infliximab treatment was terminated, the neurological symptoms and the magnetic resonance imaging changes persisted. Development of new neuropsychiatric changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…Besides the effect of anti-TNFa therapy on definite MS, a relation between anti-TNFa agents and newly onset of MS or MS-like syndromes has been documented [1326, 3538]. It is unclear, however, whether these demyelinating events are coincidental or whether they are causally associated with the use of TNFa antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the effect of anti-TNFa therapy on definite MS, a relation between anti-TNFa agents and newly onset of MS or MS-like syndromes has been documented [1326, 3538]. It is unclear, however, whether these demyelinating events are coincidental or whether they are causally associated with the use of TNFa antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lees et al have found 5 patients with CD complicated with central, axonal or peripheral demyelination in a retrospective analysis of 199 IBD patients treated with anti-TNF-a (infliximab, adalimumab, natalizumab) between 1999 and 2007 in Edinburgh [44]. Of these patients, 23 had previously been treated with anti-TNF-a (78% with infliximab) for CD [24,34,35,[44][45][46][47][48][49][50][51][52], had a mean age of 42 years (range, 18-74) and had a slight female predominance (57%). The time from last anti-TNF-a infusion until the onset of the neurological deficits varied from few hours to 4 years.…”
Section: Methodsmentioning
confidence: 91%
“…[46] Gondim et al Partial recovery [49] Nozaki et al Anti-TNF-a discontinuation [50] Ohyagi et al The similar prevalence rates and the overlapping prevalence ranges of demyelination in retrospective cohort studies between IBD patients treated with anti-TNF-a agents and in those treated with other medications do not confirm and further undermine the aforementioned hypotheses. The number of reported cases of demyelination in IBD patients treated with anti-TNF-a agents over the IBD cases of demyelination on treatment with other medications should be cautiously interpreted, as adverse events from new treatments are more likely to be reported compared to conventional ones due to the higher surveillance rates of the novel medication.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Recently, 5 new cases have been published [12,13,[16][17][18] . Although the incidence of demyelinating events with these drugs can be considered low (30 per million people per year), it is still much higher than the sporadic appearance of MS [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Although TNF-␣ antagonists have shown promising results in experimental allergic encephalomyelitis [6,7] , clinical trials with MS patients had to be suspended because of the increased number and severity of relapses [8,9] . Some cases of demyelinating events have also been noticed in relation to their use [10][11][12][13][14][15][16][17][18] . In this article, we describe a patient who presented the first attack of MS during a course of etanercept treatment (a fusion protein composed of the soluble membrane of TNF-␣ p75 and the constant fraction of IgG1) for psoriatic arthritis.…”
mentioning
confidence: 99%